Evaluation of the Impact of a Mobile Health System on Adherence to Antenatal and Postnatal Care and Prevention of Mother-to-Child Transmission of HIV Programs in Kenya - Mushamiri, Ivy; Luo, Chibulu; Iiams-Hauser, Casey; Amor, Yanis Ben (BioMed Central, 2015)
The Millennium Villages Project (MVP) implemented in Western Kenya a mobile Health tool that uses text messages to coordinate Community Health Worker (CHW) activities around antenatal care (ANC) and Prevention of Mother-to-Child Transmission of HIV (PMTCT), named the ANC/PMTCT Adherence System (APAS). End-user changes in health-seeking behavior in ANC and postnatal care (PNC) were investigated following registration of 800 women into APAS. These investigations employed interviews of pregnant women or new mothers (n = 67) and CHWs (n = 20). Ordinal logistic regressions and exact binomial tests were used in the routine data analyses (n = 650, health registers). All CHWs interviewed agreed that APAS helped them track pregnant woman efficiently, compared to paper-based tracking forms. Women registered in APAS reported that CHWs reminded them of appointments more regularly than before its inception. The APAS also greatly increased the likelihood of women making the 6 recommended post-delivery baby follow-ups.